The Role of Transformational Leadership Style, Organizational Culture, Innovative Work Behavior of Employees on Cooperative Performance - Anna Suzana; Djie Maulana Sakti; Defa Bagus Ilyas (Journal Research of Social Science, Economics, and Management, 2024)
The importance of factors such as transformational leadership, organizational culture, and innovative employee behavior in the context of cooperatives, especially the Employee Cooperative of the Republic of Indonesia (KPRI) Harapan Sejahtera IAIN Syekh Nurjati Cirebon. Although the relationship between these factors is generally recognized, specific research on them in cooperative environments is limited. Thus, this study aims to contribute knowledge by analyzing the influence of transformational leadership and organizational culture on the innovative behavior of employees at the IAIN Harapan Sejahtera Cooperative. The method used in this study is the associative method. The object of this study was a member of the HARAPAN SEJAHTERA IAIN Syekh Nurjati Cirebon Cooperative as many as 50 respondents who were taken randomly. The technique used in collecting data in this study is in the form of questionnaires, the author distributes questionnaires that can be filled directly by respondents. The results showed that there was no significant influence between Transformational Leadership Style and Cooperative Performance, while Organizational Culture and Innovative Employee Behavior had a significant influence on Cooperative Performance.